Manajemen Sosialisasi Inseminasi Buatan untuk Peningkatan Pemahaman Masyarakat Di Desa Pakijangan, Wonorejo, Kabupaten Pasuruan - Sidi Asmadi; Cakti Indra Gunawan; Budi Santosa (Ecobuss, 2023)
The change in the paradigm of thinking from traditional to modern has changed the way of life of the people, especially people who make a living as breeders. Therefore, there is a need for research on Efforts to Increase Community Understanding of Adopting Artificial Insemination (AI) in Cattle in Pakijangan Village, Wonorejo District, Pasuruan Regency. This study used a descriptive method, with a slovin sampling of 120 respondents. Data analysis includes descriptive analysis and multiple linear regression analysis. The results showed that the education level of the farmer did not affect the farmer's understanding of artificial insemination (AI) and his success in accessing information did not show a significant effect on the farmer's understanding of AI.